Rethinking School Safety in the Age of Empire: Militarization, Mental Health, and State Violence - Jaffee, Laura Jordan (Disability Studies Quarterly, 2018)
Calls for stricter gun control and mental health screening often come on the heels of school shootings, which have raised national concerns about school safety. The implication is that people with psychiatric disabilities are dangerous or threatening, and that preventing them from owning guns will make schools safer. This paper challenges this assumption by considering dominant discourses about school safety and mental health alongside the increasing militarization of U.S. schools. Advocating reducing violence by identifying individuals with psychiatric disabilities—or those labelled with mental illnesses presumed to render them dangerous—erases the profound state violence schools engender in the service of empire while perpetuating ableist assumptions about people with psychiatric disabilities. In the age of empire and endless imperialist war, we need to challenge prevailing conceptions of both school safety and mental health.